Teflon composite coating and cooker comprising same
By using graft copolymers of polyethersulfone and polyoxazoline as the bottom coating of Teflon non-stick pan, the problems of complex manufacturing and long-term use of existing coatings are solved, and better adhesion and durability are achieved.
Patent Information
- Application Number
- CN202510410613.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The existing Teflon non-stick pan coating is complex in the manufacturing process and is prone to fall off and turn yellow during long-term use, affecting the service life and appearance of the pan.
The graft copolymer of polyethersulfone and polyoxazoline is used as the base coating, and the graft copolymer is formed by introducing -CH2X groups on the benzene ring of the polyethersulfone to improve its compatibility and adhesion with polytetrafluoroethylene.
It improves adhesion between the coating and the metal substrate, reduces the risk of coating falling off, extends the durability of the coating, reduces yellowing, and improves the aesthetics of the pot.
Smart Images

Figure SMS_2 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to a Teflon coating, in particular to a Teflon composite coating and a cooker comprising the coating. Background Art
[0002] Teflon non-stick pan is a common cooking utensil, which is coated with Teflon (PTFE) coating, and has the characteristics of not easy to stick to food and easy to clean. However, due to the poor adhesion of Teflon to metal surfaces, during the manufacturing process, the Teflon coating needs to be applied to the surface of the cookware through multiple layers of materials, including a base coating, an intermediate coating and a surface coating, to ensure its durability and anti-stick performance.
[0003] The most common Teflon non-stick coating includes a surface coating of polytetrafluoroethylene, an intermediate coating of polyamide-imide (PAI), and a bottom coating of polyethersulfone (PES). Polyethersulfone has excellent heat resistance and metal surface adhesion, and can be tightly bonded to the base material of the cookware, providing good adhesion and durability, ensuring that the coating will not fall off easily during long-term use. However, due to the poor adhesion between polyethersulfone and polytetrafluoroethylene, a PAI intermediate layer needs to be added to compound polytetrafluoroethylene and polyethersulfone together. The multi-layer structure makes the manufacturing process complicated, and problems such as coating shedding and yellowing may occur during long-term use, affecting the service life and appearance of the cookware.
[0004] In addition, due to the hydrophobic nature of polyethersulfone, coatings with polyethersulfone as the main component basically need to use organic solvents as diluents. The large-scale use of organic solvents not only leads to high production costs, but also causes environmental pollution. In this case, in order to enhance the compatibility of polyethersulfone with polytetrafluoroethylene, polyethersulfone needs to be ground into ultrafine powder, but this increases the operating steps and production costs. Summary of the invention
[0005] To overcome at least one defect of the above-mentioned prior art, in a first aspect, the present invention provides a Teflon composite coating, comprising a surface layer and a bottom layer, wherein the surface layer comprises polytetrafluoroethylene, and the bottom layer comprises a graft copolymer of polyethersulfone and polyoxazoline.
[0006] In one embodiment, the graft copolymer includes a polyethersulfone backbone and polyoxazoline side chains grafted to the polyethersulfone backbone.
[0007] In one embodiment, the weight average molecular weight of the polyethersulfone main chain is 50,000 to 120,000 g / mol; and / or, In the graft copolymer, the mass content of the polyoxazoline side chains is 1 to 50%; and / or, The oxazoline monomer for preparing the polyoxazoline branch chain includes 2-methyl-2-oxazoline.
[0008] In one embodiment, the weight average molecular weight of the polyethersulfone main chain is 80,000 to 100,000 g / mol; and / or, In the graft copolymer, the mass content of the polyoxazoline side chains is 10 to 50%; and / or, The polyethersulfone has the following structural units: .
[0009] In one embodiment, the method for preparing the graft copolymer comprises the following steps: A -CH2X group is introduced into the benzene ring of polyethersulfone through reaction to obtain a polyethersulfone initiator; The graft copolymer is prepared by performing a ring-opening polymerization reaction of the oxazoline monomer using the polyethersulfone initiator; Here, X is a halogen atom.
[0010] In one embodiment, the preparation process of the polyethersulfone comprises: The reaction mixture is reacted at 140-200° C. for 2-8 hours, and then the reaction system is reacted at 160-230° C. for 2-48 hours; wherein the reaction mixture comprises a first monomer, a second monomer and a salt-forming agent; and / or, The preparation process of the polyethersulfone initiator comprises: mixing the polyethersulfone with paraformaldehyde, SnCl4 and (CH3)3SiCl and reacting at 30-60°C for 12-72h; and / or, The process of the ring-opening polymerization reaction comprises: The polyethersulfone initiator and the oxazoline monomer are reacted at 90-110° C. to obtain the graft copolymer.
[0011] In one embodiment, the molar number of -CH2X groups accounts for 5 to 50% of the total molar number of the polyethersulfone structural unit; and / or, X is a chlorine atom or a bromine atom; and / or, The salt-forming agent includes one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate; and / or, The first monomer includes bisphenol S, and the second monomer includes one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone.
[0012] In a second aspect, the present invention provides a cooking utensil comprising the above-mentioned Teflon composite coating.
[0013] In a third aspect, the present invention provides a graft copolymer of polyethersulfone and polyoxazoline, comprising a polyethersulfone main chain and a polyoxazoline side chain grafted to the polyethersulfone main chain.
[0014] In a fourth aspect, the present invention provides the use of the above-mentioned graft copolymer of polyethersulfone and polyoxazoline in the preparation of Teflon composite coatings or cookware.
[0015] The Teflon coating of the invention has good metal adhesion and low yellowness coefficient, and can be used in cookers to improve the durability and aesthetics of the coating or cookers. DETAILED DESCRIPTION
[0016] Typical embodiments that embody the features and advantages of the present invention will be described in detail in the following description. It should be understood that the present invention can have various changes in different embodiments without departing from the scope of the present invention, and the descriptions therein are essentially used as illustrations rather than to limit the present invention.
[0017] One embodiment of the present invention provides a graft copolymer of polyethersulfone and polyoxazoline (polyethersulfone- g -polyoxazoline), including a main chain and one or more branches grafted to the main chain, the main chain is polyethersulfone (i.e., polyethersulfone main chain), and the branch chain is a polyoxazoline segment (i.e., polyoxazoline branch chain).
[0018] In one embodiment, polyethersulfone is a resin comprising a sulfone group (-SO2-) and an arylene group in the main chain of the molecule.
[0019] In one embodiment, the polyethersulfone has the following structural units:
[0020] In one embodiment, the weight average molecular weight of the polyethersulfone main chain can be 50,000 to 120,000 g / mol, further can be 60,000 to 100,000 g / mol, and further can be 70,000 to 100,000 g / mol, for example, 60,000 g / mol, 70,000 g / mol, 71,000 g / mol, 72,000 g / mol, 75,000 g / mol, 80,000 g / mol, 85,000 g / mol, 90,000 g / mol, 92,000 g / mol, 93,000 g / mol, 94,000 g / mol, 95,000 g / mol, 105,000 g / mol, and 110,000 g / mol.
[0021] In one embodiment, in the graft copolymer of polyether sulfone and polyoxazoline, the mass content of polyoxazoline side chains can be 1-50%, further can be 10-50%, further can be 35-50%, for example 2%, 6%, 8%, 10%, 10.5%, 11%, 12%, 15%, 18%, 25%, 30%, 35%, 40%, 45%. Wherein, the content of polyoxazoline side chains in the graft copolymer can be regulated by controlling the molar ratio of oxazoline monomer to polyether sulfone.
[0022] In one embodiment, the monomers for preparing the polyethersulfone (main chain) include a first monomer and a second monomer, the first monomer includes bisphenol S, and the second monomer includes one or more of dichlorodiphenyl sulfone (e.g., 4,4'-dichlorodiphenyl sulfone) and difluorodiphenyl sulfone (e.g., 4,4'-difluorodiphenyl sulfone). Further, the polyethersulfone can be prepared by a nucleophilic substitution reaction of the monomers.
[0023] In one embodiment, the oxazoline monomer used to prepare the polyoxazoline branches includes 2-methyl-2-oxazoline.
[0024] In one embodiment, the preparation process of the graft copolymer of polyethersulfone and polyoxazoline includes: first preparing polyethersulfone, then introducing a -CH2X group on the benzene ring of polyethersulfone by reaction to obtain a polyethersulfone initiator; then initiating the ring-opening polymerization of the oxazoline monomer through the -CH2X group in a grafting manner, for example, it can be a cationic ring-opening polymerization.
[0025] In one embodiment, X in the -CH2X group (benzyl halide) on the benzene ring of the polyethersulfone initiator is a halogen atom, such as chlorine or bromine.
[0026] In one embodiment, the molar number of -CH2X groups on the benzene ring of the polyethersulfone initiator accounts for 5-50% of the total molar number of polyethersulfone structural units (or repeating units), for example 5%, 10%, 13%, 14%, 15%, 16%, 17%, 20%, 25%, 30%, 35%, 40%, 45%, 50%.
[0027] One embodiment of the present invention provides a method for preparing the above-mentioned graft copolymer of polyethersulfone and polyoxazoline, comprising the following steps: A -CH2X group is introduced into the benzene ring of polyethersulfone through reaction to obtain a polyethersulfone initiator; The graft copolymer is prepared by ring-opening polymerization of oxazoline monomers using polyethersulfone initiator; Here, X is a halogen atom (eg, a chlorine atom).
[0028] In one embodiment, polyethersulfone can be prepared by reacting a first monomer and a second monomer. Further, the preparation process of polyethersulfone includes: The reaction mixture is reacted at 140-200° C. (first reaction temperature) for 2-8 hours, and then the reaction system is reacted at 160-230° C. (second reaction temperature) for 2-48 hours; wherein the reaction mixture includes a first monomer, a second monomer and a salt-forming agent.
[0029] In one embodiment, the weight average molecular weight of the polyethersulfone is the same as the molecular weight of the polyethersulfone backbone, and the molecular weight distribution of the polyethersulfone is 1.50 to 2.50, for example, 1.50, 1.60, 1.65, 1.67, 1.70, 1.71, 1.80, 1.90, 2.00, 2.10, 2.20, 2.30, 2.40, and 2.50.
[0030] In one embodiment, the amount ratio of the first monomer to the second monomer can be 1:1.0 to 1:1.03; the amount of the salt-forming agent can be 1.05 to 1.3 times the amount of the first monomer, for example, 1.1 times, 1.15 times, 1.2 times, or 1.25 times.
[0031] In one embodiment, the reaction mixture for preparing the polyethersulfone containing an initiating group includes a first monomer, a second monomer, a salt-forming agent, and an organic solvent, and the organic solvent may include a first organic solvent.
[0032] In one embodiment, the organic solvent used in the preparation process of polyethersulfone includes a first organic solvent and a second organic solvent; the preparation process of polyethersulfone may include the following steps: Mixing the first monomer, the second monomer, the salt-forming agent, the first organic solvent, and the second organic solvent to obtain a reaction mixture; and The reaction mixture is refluxed at 140-200° C. for 2-8 hours, the second organic solvent is then evaporated, and the reaction system is reacted at 160-230° C. for 2-48 hours.
[0033] In one embodiment, the first monomer, the second monomer, and the salt-forming agent may be immersed in the first organic solvent in sequence, and then the second organic solvent is added to the system under stirring.
[0034] In one embodiment, the amount of the first organic solvent used is such that the solid content of the reaction system reaches 20-45wt% (e.g., 25wt%, 30wt%, 35wt%, 40wt%), and the amount of the second solvent used is 0-20wt% (e.g., 1wt%, 2wt%, 5wt%, 10wt%, 15wt%) of the first solvent.
[0035] In one embodiment, during the preparation of polyethersulfone, the first reaction temperature may be, for example, 150°C, 160°C, 170°C, 180°C, 190°C, and the reaction time of the system at the first reaction temperature may be, for example, 3h, 4h, 5h, 6h or 7h.
[0036] In one embodiment, during the preparation of polyethersulfone, the second reaction temperature can be, for example, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, and the reaction time of the system at the second reaction temperature can be, for example, 3h, 3.5h, 4h, 5h, 6h, 8h, 10h, 12h, 15h, 20h, 25h, 30h, 35h, 40h, 45h.
[0037] In one embodiment, during the preparation of polyethersulfone, after the reaction at the first reaction temperature is completed, the second organic solvent in the reaction system can be evaporated by increasing the system temperature.
[0038] In one embodiment, during the preparation of polyethersulfone, after the reaction at the second reaction temperature is completed, a capping agent is added to the system, followed by post-treatment, which may include filtering, crushing, washing, and vacuum drying the reaction fluid.
[0039] In one embodiment, the first monomer may be bisphenol S, the second monomer may be one or more of dichlorodiphenyl sulfone (eg, 4,4'-dichlorodiphenyl sulfone) and difluorodiphenyl sulfone (eg, 4,4'-difluorodiphenyl sulfone), and the oxazoline monomer may be 2-methyl-2-oxazoline.
[0040] In one embodiment, the salt-forming agent may include one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate. Further, the salt-forming agent may be potassium carbonate and / or sodium carbonate.
[0041] In one embodiment, the first organic solvent may include dimethyl sulfoxide, dimethyl sulfone, N , N -dimethylformamide, N , N -Dimethylacetamide, N - one or more of methyl pyrrolidone and sulfolane.
[0042] In one embodiment, the second organic solvent may include one or more of toluene, xylene, o-xylene, and chlorobenzene.
[0043] In one embodiment, the end-capping agent may include one or more of methyl chloride, ethyl chloride, and 4-chlorodiphenyl sulfone. Further, the end-capping agent may be methyl chloride.
[0044] In one embodiment, the preparation process of the polyethersulfone initiator includes: mixing polyethersulfone with paraformaldehyde, SnCl4 and (CH3)3SiCl and reacting at 30-60°C for 12-72h. Further, the reaction temperature can be, for example, 35°C, 40°C, 45°C, 50°C or 55°C; the reaction time can be, for example, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h or 70h.
[0045] In one embodiment, the mass ratio of polyethersulfone to paraformaldehyde, SnCl4, and (CH3)3SiCl can be 100:30-40:2-4:100-140.
[0046] In one embodiment, the preparation process of the polyethersulfone initiator includes: dissolving polyethersulfone in a third organic solvent, adding polyformaldehyde, SnCl4 and (CH3)3SiCl to the formed solution, and reacting at 30-60°C for 12-72 hours; precipitating the reaction mixture in methanol, then filtering and separating the polymer, then dissolving the obtained polymer in a fourth organic solvent, and reprecipitating it through a fifth organic solvent, and then filtering and drying it under vacuum conditions.
[0047] In one embodiment, the third organic solvent may be one or more of chloroform (trichloromethane), dichloromethane, and tetrahydrofuran; the fourth organic solvent may be one or more of chloroform (trichloromethane), dichloromethane, and tetrahydrofuran; and the fifth organic solvent may be methanol and / or ethanol.
[0048] In one embodiment, the molar number of -CH2X groups on the benzene ring of the polyethersulfone initiator accounts for 5-50% of the total molar number of the polyethersulfone structural unit (or repeating unit), and the value of the molar content can be adjusted by feed ratio, reaction time, etc.
[0049] In one embodiment, the process of the ring-opening polymerization of the oxazoline monomer comprises: reacting a polyethersulfone initiator and an oxazoline monomer at 90 to 110° C. to obtain a graft copolymer.
[0050] In one embodiment, the ring-opening polymerization reaction temperature of the oxazoline monomer can be 92°C, 95°C, 98°C, 100°C, 102°C, 105°C, 108°C; the time can be 0.5 to 6 hours, for example 0.5h, 1h, 2h, 3h, 4h, 5h, 6h.
[0051] In one embodiment, the ring-opening polymerization reaction of the oxazoline monomer may be performed in a nitrogen atmosphere.
[0052] In one embodiment, the oxazoline monomer may be 2-methyl-2-oxazoline. Further, the grafting density of the graft copolymer may be adjusted by controlling the amount of oxazoline monomer added and the conversion rate, for example, by extending the reaction time, the conversion rate may reach 100%, and after the polymerization is completed, the system may completely change from liquid to solid.
[0053] In one embodiment, the amount of the oxazoline monomer may be 1-50% of the mass of the polyethersulfone, such as 1%, 5%, 10%, 20%, 30%, 40%, 50%.
[0054] An embodiment of the present invention provides a Teflon composite coating, comprising a surface layer and a bottom layer, wherein the surface layer comprises polytetrafluoroethylene, and the bottom layer comprises the above-mentioned graft copolymer of polyethersulfone and polyoxazoline.
[0055] In one embodiment, the graft copolymer of polyethersulfone and polyoxazoline comprises a polyethersulfone main chain and polyoxazoline side chains grafted onto the polyethersulfone main chain.
[0056] In one embodiment, the Teflon composite coating is disposed on the surface of the cookware through a base layer.
[0057] In one embodiment, the preparation method of the graft copolymer film (or layer) of polyethersulfone and polyoxazoline comprises the following steps: 15-35 parts by weight of a graft copolymer of polyethersulfone and polyoxazoline, 35-55 parts by weight of water and 10-50 parts by weight of a sixth organic solvent are mixed to form a dispersion; the dispersion is dried at a temperature of 200-380° C. to form a film.
[0058] In one embodiment, the sixth organic solvent may be one or more of chloroform, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0059] In one embodiment, the thickness of the graft copolymer membrane of polyethersulfone and polyoxazoline may be 10 to 2000 μm, for example, 50 μm, 100 μm, 200 μm, 500 μm, 800 μm, 1000 μm, 1200 μm, 1500 μm, or 1800 μm.
[0060] In one embodiment, the yellowness index of the graft copolymer film of polyethersulfone and polyoxazoline is less than 10, and may further be 4-5.
[0061] One embodiment of the present invention provides a cooker, comprising the above-mentioned Teflon composite coating or the above-mentioned graft copolymer of polyethersulfone and polyoxazoline.
[0062] In one embodiment, the cookware is a utensil for cooking (such as a non-stick pan), and the Teflon composite coating is at least disposed on the inner surface of the cookware.
[0063] One embodiment of the present invention provides the use of the above-mentioned graft copolymer of polyethersulfone and polyoxazoline (or the graft copolymer membrane of polyethersulfone and polyoxazoline) in the preparation of Teflon composite coating.
[0064] The graft copolymer of polyethersulfone and polyoxazoline in one embodiment of the present invention is an amphiphilic copolymer comprising a hydrophobic polyethersulfone main chain and a hydrophilic polyoxazoline side chain, which can be well dissolved in polar organic solvents and has good film-forming properties.
[0065] The graft copolymer membrane of polyethersulfone and polyoxazoline according to one embodiment of the present invention has better metal adhesion and lower yellowness index than the polyethersulfone membrane.
[0066] The graft copolymer of polyethersulfone and polyoxazoline according to one embodiment of the present invention has the characteristics of good compatibility with polytetrafluoroethylene, low yellowness index and excellent water dispersibility. The graft copolymer of polyethersulfone and polyoxazoline has a stable structure, and its application in Teflon coating can effectively improve the adhesion between the coating and the applied substrate (such as metal) and reduce the risk of coating shedding.
[0067] In the Teflon coating of one embodiment of the present invention, the presence of polyoxazoline improves the yellowing resistance of the coating, so that the coating can still maintain its original color after long-term use.
[0068] The Teflon coating of one embodiment of the present invention may include a two-layer structure, and the spraying process is simpler than the existing three-layer coating; and it also has better adhesion and low yellowness coefficient, which improves the durability and aesthetics of the coating. The above characteristics solve the problems of the existing coating, such as the complicated spraying process (three layers), the coating is easy to fall off from the applied substrate and yellowing after long-term use, and the poor hydrophilicity of polyethersulfone.
[0069] The preparation and application of the graft copolymer of polyethersulfone and polyoxazoline according to one embodiment of the present invention are further described below in conjunction with examples. Part of the raw materials and test methods involved in each example are as follows.
[0070] raw material Bisphenol S was purchased from Jiangsu Aolunda Technology Industry Co., Ltd.; dichlorodiphenyl sulfone was purchased from Hebei Jianxin Chemical Co., Ltd.; and the salt-forming agent was purchased from Haihua Group.
[0071] Test Method 1. Weight average molecular weight and molecular weight distribution The molecular weight of polyethersulfone was determined by gel permeation chromatography (GPC), with DMF containing 20 mmol lithium bromide as the mobile phase, PMMA as the standard sample, and Agilent MIXD C, MIXD D, and MIXD E columns connected in series at a flow rate of 1.0 mL / min.
[0072] 2. Adhesion test to metal Polyethersulfone- g -The dispersion of polyoxazoline was sprayed on the cleaned metal surface to form a coating, and the adhesion between the coating and the metal was tested according to the ASTM D3359 cross-sectional test method.
[0073] 3. Yellowness test The yellowness index was tested according to ASTM E313 (2mm).
[0074] Example 1 Preparation of polyethersulfone 1001.1g of bisphenol S, 1159.9g of 4,4'-dichlorodiphenyl sulfone and 635.7g of potassium carbonate were added to 3446.8g of cyclobutane sulfone in sequence, and then 1723.3g of xylene was added to the reactor under stirring, and the mixture was heated to 160°C (first reaction temperature) and refluxed for 5h. When no water was produced, the temperature was increased to completely evaporate the xylene in the reactor, and then the mixture was reacted at 220°C (second reaction temperature) for 3.5h. After that, methyl chloride was introduced for a 30min end-capping reaction. Finally, the obtained reaction liquid was filtered, crushed, washed with water and vacuum dried to obtain polyether sulfone.
[0075] Preparation of polyethersulfone initiator 100g of the polyethersulfone prepared above was dissolved in 2.5L of chloroform, 33.6g of paraformaldehyde, 2.94g of SnCl4 and 142.8mL of (CH3)3SiCl were added to the completely dissolved solution, and then reacted at 40°C for 72h; the obtained reaction mixture was precipitated in methanol, the polymer was separated by filtration, and then the polymer was dissolved in 2.5L of chloroform and reprecipitated in methanol, filtered and dried under vacuum for 24h to obtain a polyethersulfone initiator. The molar number of -CH2X groups on the benzene ring of the polyethersulfone initiator accounted for 15% of the total molar number of the polyethersulfone structural unit.
[0076] Polyethersulfone- g Preparation of polyoxazoline graft copolymers Under nitrogen atmosphere, 50 g of the polyethersulfone initiator prepared above was added to a reaction bottle, and the resulting mixture was mixed with 6 mL of 2-methyl-2-oxazoline monomer, and then the system was heated to 100° C. to initiate bulk polymerization of the oxazoline monomer. After reacting for 2 h, the polymerization was terminated with 2 mL of NaOH aqueous solution (0.2 mol / L). The reacted material was vacuum dried to constant weight to obtain a graft copolymer of polyethersulfone and polyoxazoline (PES- g -PMOX), whose structural formula is as follows:
[0077] The polyethersulfone prepared according to the above method was tested, and its weight average molecular weight was 91540 g / mol, and the molecular weight distribution was 1.70; the mass content of the poly(2-methyl-2-oxazoline) branched chain was calculated to be 10.6%.
[0078] Polyethersulfone- g -Preparation of polyoxazoline membrane 30 parts by mass of the polyethersulfone prepared above g -Polyoxazoline powder, 35 parts by mass of water, and 35 parts by mass of N-methylpyrrolidone were mixed and stirred to form polyethersulfone- g -polyoxazoline dispersion, the dispersion is dried at a high temperature of 350°C to form a film with a thickness of 200 μm.
[0079] According to the above method, polyethersulfone- g -Polyoxazoline dispersion was sprayed on the metal surface for adhesion test. The results showed that the adhesion between the film and the metal met the ASTM grade 5B requirements. g -The polyoxazoline film was tested for yellowness, and the yellowness index was 5.
[0080] Heat polytetrafluoroethylene to a molten state, add the polyethersulfone- g -poly(2-methyl-2-oxazoline) powder was stirred, and the polyethersulfone powder could adhere to the surface of polytetrafluoroethylene without stratification, indicating that polytetrafluoroethylene and polyethersulfone- g -Poly (2-methyl-2-oxazoline) has better adhesion.
[0081] Example 2 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- g -polyoxazoline and its membrane, the only difference is that: in the preparation of polyethersulfone, N-methylpyrrolidone is used instead of cyclopentane, and xylene is not added; the second reaction temperature is 200°C, and the reaction time is 5h.
[0082] The polyethersulfone prepared according to the above method was tested, and its weight average molecular weight was 90980 g / mol, and the molecular weight distribution was 1.71; the mass content of the poly(2-methyl-2-oxazoline) branch chain was calculated to be 10.6%.
[0083] The same method as in Example 1 was used to prepare polyethersulfone- g -Test on the adhesion of polyoxazoline to metals. The results show that it meets the requirements of ASTM Grade 5B.
[0084] The same method as in Example 1 was used to prepare polyethersulfone- g - Yellowness test of polyoxazoline film, yellowness index is 5.
[0085] The same method as in Example 1 was used to prepare polyethersulfone- g - Adhesion Test of Poly(2-methyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- g -Poly (2-methyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.
[0086] Example 3 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- g -polyoxazoline and its membrane, the only difference is that 10 mL of 2-methyl-2-oxazoline monomer is added during the preparation of the graft copolymer.
[0087] The polyethersulfone prepared according to the above method was tested, and its weight average molecular weight was 91965 g / mol, and the molecular weight distribution was 1.73; the mass content of poly(2-methyl-2-oxazoline) branches was calculated to be 16.5%.
[0088] The same method as in Example 1 was used to prepare polyethersulfone- g -Test on the adhesion of polyoxazoline to metals. The results show that it meets the requirements of ASTM Grade 5B.
[0089] The same method as in Example 1 was used to prepare polyethersulfone- g - Yellowness test of polyoxazoline film, yellowness index is 5.
[0090] The same method as in Example 1 was used to prepare polyethersulfone- g - Adhesion Test of Poly(2-methyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- g -Poly (2-methyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.
[0091] Example 4 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone-g -polyoxazoline and its membrane, the only difference being that 30 mL of 2-methyl-2-oxazoline monomer was added during the preparation of the graft copolymer.
[0092] The polyethersulfone prepared according to the above method was tested, and its weight average molecular weight was 92080 g / mol, and the molecular weight distribution was 1.68; the mass content of the poly(2-methyl-2-oxazoline) branch chain was calculated to be 37.2%.
[0093] The same method as in Example 1 was used to prepare polyethersulfone- g -Test on the adhesion of polyoxazoline to metals. The results show that it meets the requirements of ASTM Grade 5B.
[0094] The same method as in Example 1 was used to prepare polyethersulfone- g - Yellowness test of polyoxazoline film, yellowness index is 4.
[0095] The same method as in Example 1 was used to prepare polyethersulfone- g - Adhesion Test of Poly(2-methyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- g -Poly (2-methyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.
[0096] Example 5 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- g -polyoxazoline and its membrane, the only difference is that 45 mL of 2-methyl-2-oxazoline monomer is added during the preparation of the graft copolymer.
[0097] The polyethersulfone prepared according to the above method was tested, and its weight average molecular weight was 91055 g / mol, and the molecular weight distribution was 1.69; the mass content of poly(2-methyl-2-oxazoline) branches was calculated to be 47.0%.
[0098] The same method as in Example 1 was used to prepare polyethersulfone- g -Test on the adhesion of polyoxazoline to metals. The results show that it meets the requirements of ASTM Grade 5B.
[0099] The same method as in Example 1 was used to prepare polyethersulfone- g - Yellowness test of polyoxazoline film, yellowness index is 4.
[0100] The same method as in Example 1 was used to prepare polyethersulfone- g - Adhesion Test of Poly(2-methyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- g-Poly (2-methyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.
[0101] Example 6 This example uses the same raw materials and process as Example 1 to prepare polyethersulfone- g - polyoxazoline and its membrane, the only difference is that in the preparation of polyethersulfone, the second reaction time is 3h.
[0102] The polyethersulfone prepared according to the above method was tested, and its weight average molecular weight was 71850 g / mol, and the molecular weight distribution was 1.67; the mass content of poly(2-methyl-2-oxazoline) branches was calculated to be 10.6%.
[0103] The same method as in Example 1 was used to prepare polyethersulfone- g -Test on the adhesion of polyoxazoline to metals. The results show that it meets the requirements of ASTM Grade 5B.
[0104] The same method as in Example 1 was used to prepare polyethersulfone- g - Yellowness test of polyoxazoline film, yellowness index is 4.
[0105] The same method as in Example 1 was used to prepare polyethersulfone- g - Adhesion Test of Poly(2-methyl-2-oxazoline) to Polytetrafluoroethylene, Polyethersulfone- g -Poly (2-methyl-2-oxazoline) can adhere to the surface of polytetrafluoroethylene without delamination, indicating that the two have good adhesion.
[0106] Comparative Example 1 Preparation of polyethersulfone membrane 30 parts by mass of the polyethersulfone powder prepared in Example 1, 35 parts by mass of water and 35 parts by mass of N-methylpyrrolidone were mixed and stirred to form a polyethersulfone dispersion, and the dispersion was dried at a high temperature of 350° C. to form a film with a thickness of 200 μm.
[0107] The polyethersulfone dispersion was subjected to an adhesion test according to the aforementioned method, and the results showed that it met the ASTM grade 3B requirements. The polyethersulfone was subjected to a yellowness test according to the aforementioned method, and the yellowness index was 16.
[0108] When polytetrafluoroethylene is heated to a molten state and polyethersulfone powder is added and stirred, the polyethersulfone powder cannot adhere to the surface of polytetrafluoroethylene and the two are separated into layers, indicating that the adhesion between polytetrafluoroethylene and polyethersulfone is poor.
[0109] Table 1 lists the differences and performance parameters of the polymer films of various embodiments and comparative example 1.
[0110] Table 1 Structural parameters and performance parameters of polymer films of various embodiments and comparative example 1
[0111] According to the results of Example 1 and Comparative Example 1 in Table 1, compared with Comparative Example 1, the embodiment of the present invention uses a graft copolymer of polyethersulfone and polyoxazoline as the bottom layer of the Teflon composite coating, which can make the coating have better adhesion and low yellowness coefficient, thereby improving the durability and aesthetics of the coating.
[0112] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0113] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A Teflon composite coating, characterized in that: The invention comprises a surface layer and a bottom layer, wherein the surface layer comprises polytetrafluoroethylene, and the bottom layer comprises a graft copolymer of polyethersulfone and polyoxazoline.
2. The Teflon composite coating according to claim 1, characterized in that: The graft copolymer comprises a polyethersulfone main chain and a polyoxazoline side chain grafted to the polyethersulfone main chain.
3. The Teflon composite coating according to claim 2, characterized in that: The weight average molecular weight of the polyethersulfone main chain is 50,000 to 120,000 g / mol; and / or, In the graft copolymer, the mass content of the polyoxazoline side chains is 1 to 50%; and / or, The oxazoline monomer for preparing the polyoxazoline branch chain includes 2-methyl-2-oxazoline.
4. The Teflon composite coating according to claim 2, characterized in that: The weight average molecular weight of the polyethersulfone main chain is 80,000 to 100,000 g / mol; and / or, In the graft copolymer, the mass content of the polyoxazoline side chains is 10 to 50%; and / or, The polyethersulfone has the following structural units: 。 5. The Teflon composite coating according to claim 4, characterized in that: The preparation method of the graft copolymer comprises the following steps: A -CH2X group is introduced into the benzene ring of polyethersulfone through reaction to obtain a polyethersulfone initiator; The graft copolymer is prepared by performing a ring-opening polymerization reaction of the oxazoline monomer using the polyethersulfone initiator; Here, X is a halogen atom.
6. The Teflon composite coating according to claim 5, characterized in that: The preparation process of the polyethersulfone comprises: The reaction mixture is reacted at 140-200° C. for 2-8 hours, and then the reaction system is reacted at 160-230° C. for 2-48 hours; wherein the reaction mixture comprises a first monomer, a second monomer and a salt-forming agent; and / or, The preparation process of the polyethersulfone initiator comprises: mixing the polyethersulfone with paraformaldehyde, SnCl4 and (CH3)3SiCl and reacting at 30-60°C for 12-72h; and / or, The process of the ring-opening polymerization reaction comprises: The polyethersulfone initiator and the oxazoline monomer are reacted at 90-110° C. to obtain the graft copolymer.
7. The Teflon composite coating according to claim 6, characterized in that: The molar number of -CH2X groups accounts for 5 to 50% of the total molar number of the polyethersulfone structural unit; and / or, X is a chlorine atom or a bromine atom; and / or, The salt-forming agent includes one or more of sodium hydroxide, potassium hydroxide, cesium hydroxide, potassium carbonate, sodium carbonate, cesium carbonate, potassium bicarbonate, and sodium bicarbonate; and / or, The first monomer includes bisphenol S, and the second monomer includes one or more of dichlorodiphenyl sulfone and difluorodiphenyl sulfone.
8. A cooking utensil, characterized in that: The invention comprises the Teflon composite coating according to any one of claims 1 to 7.
9. A graft copolymer of polyethersulfone and polyoxazoline, characterized in that: The invention comprises a polyethersulfone main chain and a polyoxazoline side chain grafted on the polyethersulfone main chain.
10. Use of the graft copolymer of polyethersulfone and polyoxazoline according to claim 9 in the preparation of Teflon composite coatings or cookware.
Citation Information
Patent Citations
Materials coated with antifouling paint
CN1229820A
Membrane and use thereof
CN1705506A
Thermoplastic resin composition
JP1995216207A
LED lamp device having excellent heat radiation property by using carbon nanotube
KR101483758B1
Multi-layered film and method for preparing the same
KR1020130135509A